A Radiation-Induced Meningioma “Cures” A Complex Dural Arteriovenous Fistula - Copeland, William R.; Link, Michael J. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Objective We report a case of spontaneous thrombosis of an extremely complex dural arteriovenous fistula (DAVF), believed to be previously incurable, after the development of a radiation-induced meningioma resulting from prior attempts to treat the fistula with radiosurgery.Methods A very large DAVF was treated over the course of 3 decades with a combination of partial embolization and stereotactic radiosurgery with no angiographic or clinical treatment response at long-term follow-up. However, with the development of new neurologic symptoms 13 years after radiosurgery, a meningioma was found to have arisen in the previously irradiated field, and surprisingly, the fistula had spontaneously thrombosed. The meningioma was successfully removed.Results We discuss the unique pathophysiology of the radiation-induced meningioma causing this previously incurable DAVF progressing to obliteration. We also review the natural history of DAVFs, including reported rates of spontaneous occlusion, as well as the success of radiosurgery in their treatment. Finally, the incidence of radiosurgery-induced tumors, particularly meningiomas, is reviewed.Conclusion The relationship between the spontaneous thrombosis of a DAVF and the radiation-induced meningioma is unique and has not previously been reported.
Keywords: dural arteriovenous fistula; spontaneous thrombosis; radiation-induced meningioma; radiosurgery